Functionalized multi-walled carbon nanotubes/hydrogen-rich benzoxazine nanocomposites for cosmic radiation shielding with enhanced mechanical properties and space environment resistance. (29th September 2022) - Cha, Ji-Hun; Jang, Woo-Hyeok; Sarath Kumar, Sathish Kumar; Noh, Jung-Eon; Choi, Joo-Seung; Kim, Chun-Gon
Abstract: In the new space era, cosmic radiation shielding is important for satellites equipped with highly integrated electronic equipment and astronauts participating in long-term space missions. Because hydrogen-rich benzoxazine (HRB) contains a large amount of hydrogen, it can effectively shield radiation. The mass of an HRB radiation shield is lower than that of an epoxy shield, and its mechanical properties may be enhanced by the addition of amines or carbon nanotubes. However, when HRB is exposed to a space environment, high-energy atomic oxygen erodes its surface, while ultrahigh vacuum combined with high temperature causes outgassing. To improve the mechanical properties of HRB and its space environment resistance, multi-walled carbon nanotube (MWCNT)/HRB nanocomposites with grafted amine groups have been synthesized in this study. The tensile properties of these nanocomposites were evaluated, and their space environment resistance was determined using special equipment that simulates a space environment, including high-energy atomic oxygen irradiation. The obtained results revealed that the proposed NH2 –MWCNT/HRB nanocomposites were superior to HRB in terms of their tensile properties, outgassing performance, and atomic oxygen resistance. Therefore, these materials can potentially replace epoxy polymers in space missions that require cosmic radiation shielding. Graphical abstract: Image 1